Analysis of pediatric patient admitted through Emergency at Patan Hospital, Nepal - Acharya, Samita; Shrestha, Ashis (Journal of General Practice and Emergency Medicine of Nepal, 2010)
Introduction: It is very important to know the important causes of emergency visit of children and mortality. Identifying diseases which are common and severe enables planners to design proper priority setting and intervention planning. Methods: This is a descriptive retrospective study done at Patan Hospital reviewing files of Pediatric patients admitted from Poush 2065 to Mangshir 2066 (December 2008 to December 2009). Results: Out of 612 records selected, top five causes of hospital admission observed were Pneumonia 25.8%, Acute gastroenteritis 12.7%, Neonatal sepsis 12.3%, Febrile Seizure 12.1% and Enteric Fever 4.7%. The mean hospital stay observed was 4.93 days with SD 4.73 days. In this study mortality rate was 2.1% with major causes being Severe Sepsis 38.4% and Severe Pneumonia 30.7%. Conclusions: In this study Pneumonia is found to be the common cause of pediatric admission and also contributes significantly in mortality